El mito celta del Héroe Fundador en los orígenes del Señorío de Vizcaya (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Analysis of mythical-historical legends about the origin of the Lordship of Biscay, based on comparative literature and mythology. Pro- tagonists and themes of these narrations are characteristic of Celtic literature and reveal an underlying Celtic mythological background, previously ignored, in the popular imaginary of Basque people.This analysis of Celtic-Basque literature offers logical difficulties dues to the contaminations sustained over time, but the differentiation of this Celtic-Basque literature from the Euskaldun one represents a clear progress, be- cause until now both were confused. This important Celtic-Basque literary tradition has its roots in the Celtic peoples of Basque Country in Antiquity. It allows a better understanding of the origins of the Basque literature, and con- firms the linguistics, archaeological and DNA data on the ethnogenesis of the Basque Country, which offers very deep Celtic roots.
Keywords: Celtic Literature; Celtic Mythology; Founding Hero; Basque Literature; Lordship of Biscay